2018
DOI: 10.1136/jclinpath-2017-204727
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rare diseases by screening a population selected on the basis of routine pathology results—the PATHFINDER project: lysosomal acid lipase/cholesteryl ester storage disease substudy

Abstract: Pathology databases hold routine information that can be used to identify patients with specific patterns of results or those who had biopsies to allow targeted testing for possible causes of disease. Biochemical screening suggests that the gene frequency of LAL deficiency in adults is less than 1 in 100.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…A recent UK-based study among a cohort (n-1825 patients) with dyslipidaemia and elevated transaminases failed to identify a case of LAL deficiency. 8 Liver biopsies from six of the study patients enabled DNA extraction from four cases; two of these were found to be homozygous for the LAL c.46A>C;p.Thr16Pro…”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%
“…A recent UK-based study among a cohort (n-1825 patients) with dyslipidaemia and elevated transaminases failed to identify a case of LAL deficiency. 8 Liver biopsies from six of the study patients enabled DNA extraction from four cases; two of these were found to be homozygous for the LAL c.46A>C;p.Thr16Pro…”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%
“…As such, it is worthwhile to investigate LALdeficiency in young lean-NAFLD patients with severe hypercholesterolemia (LDL higher than 160 mg/dL or 130 mg/dL in patients taking lipid-lowering drugs; and HDL lower than 40 mg/dL in men and 50 mg/dL in women), with cryptogenic cirrhosis, or with liver biopsy that shows microvesicular steatosis [152] . In fact, one third of patients with microvesicular steatosis or cryptogenic cirrhosis may have LAL-deficiency [153] .…”
Section: Hepatic Steatosis As a Manifestation Of Other Liver Diseasesmentioning
confidence: 99%
“…Identification of patients with rare diseases is problematic as the possibility of the rare disease has to be considered before a highly specialist test is ordered. The PATHFINDER project is based on the premise of using routine laboratory results to identify patients who should be tested for inherited errors of metabolism 6‐8 . The objective of this study was to use a biomarker panel comprising ferritin concentration, ALP levels and platelet count for initial screening to identify patients with potential GD from primary care or outpatient laboratory samples.…”
Section: Introductionmentioning
confidence: 99%